IMPLEMENTASI REPRESENTASI MATEMATIS DALAM PEMBELAJARAN MATEMATIKA SEKOLAH - Hapizah Hapizah; Ely Susanti; Puji Astuti (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
Mathematics can be represented by many forms such as symbolical, verbal, graphical, or tabular representations. To understand mathematics concepts is by connecting or translating all kind of mathematics representations. Therefore, mathematics teachers should facilitate students to translation all kind of mathematics representations. This article discusses the research results which investigated how mathematics teachers implement their teaching which facilitate students to translation mathematics representations. Data were collected by questionnaire, documentation, and observation. Sample of the research were 91 mathematics teachers of junior and senior high schools from some regions of South Sumatera and Bangka Belitung. The research results show that mathematics teachers have already implemented mathematics representation properly, however representations used by the teachers were not variably, which means translations between representations were not implemented yet. By comparing all mathematics representations, the symbolical representation was the most frequently used in teaching and learning. Mathematics teachers whom did not or poorly implemented mathematics representations in their teaching considered the national examination not requiring variation of the representations.